Harley Quinn. The complete first and second seasons [videorecording (Blu-Ray)] - Halpern, Justin, 1980-; Schumacker, Patrick; Lorey, Dean (Warner Bros. Entertainment Inc., 2022)
"Harley Quinn (Kaley Cuoco) has finally broken things off once and for all with the Joker (Alan Tudyk) and attempts to make it on her own as the criminal Queenpin of Gotham City in this half-hour adult animated action-comedy series. With the help of Poison Ivy (Lake Bell) and a ragtag crew of DC castoffs, Harley tries to earn a seat at the biggest table in villainy: the Legion of Doom. Don't worry -- she's got this. Or does she? In Season 2, Harley has defeated the Joker, and Gotham City is hers for the taking ... what's left of it, that is. Her celebration in the newly created chaos is cut short when Penguin, Bane, Mr. Freeze, The Riddler and Two-Face join forces to restore order in the criminal underworld. Calling themselves the Injustice League, they're intent on keeping Harley and her crew from taking control as the top villains in Gotham."--Container